Correlation risk analysis of serum Amyloid A, Procalcitonin and IFN-β2 in adverse outcomes of acute pancreatitis: Serum Amyloid A, Procalcitonin and IFN-β2 levels in acute pancreatitis - Yu, Naibo; Han, Ruxia; Chen, Menghui; Li, Xuke; Wang, Kangjian (Journal of Medical Biochemistry, 2026)
[Objective] To investigate the relationships between the severity and prognosis of individuals with acute pancreatitis (AP) and the levels of serum amyloid A, procalcitonin, and ‌interferon-β2 (IFN-β2). [Methods] 224 AP patients who were admitted to our hospital between February 2022 and February 2024 were chosen to serve as research participants. According to the Acute Physiology and Chronic Health Evaluation II (APACHE II) score, the patients were divided into a mild AP group (140 patients) and a severe AP group (84 patients). The levels of serum amyloid A, CRP, procalcitonin and IFN-β2 in the two groups were compared, and the relationships between the levels of serum amyloid A, CRP, procalcitonin and IFN-β2 and the severity of the disease were analyzed via Spearman correlation. The factors affecting the prognosis of AP patients were examined using binary logistic regression, receiver operating characteristic (ROC) curves were used to evaluate the prognostic significance of serum amyloid A, CRP, procalcitonin, and IFN-β2 for the prognosis of AP patients. [Results] The levels of serum amyloid A, CRP, procalcitonin and IFN-β2 in the mild AP group were significantly lower than those in the severe AP group (P<0.05). The severity of AP was favorably connected with serum amyloid A, CRP, procalcitonin, and IFN-β2 levels (r=0.774, 0.678, 0.830, 0.584, P<0.05). After 28 days of follow-up, among 224 AP patients, 64 patients (28.57%) had poor prognoses, including 20 patients (8.93%) with respiratory insufficiency, 24 patients (10.71%) with hypocalcemia, and 20 patients (8.93%) who died. The severe AP group also had a higher overall incidence of poor prognosis than the moderate AP group (P<0.05). AP patients’ poor prognosis was revealed to be influenced by the APACHE II score and blood levels of serum amyloid A, CRP, procalcitonin, and IFN-β2 (P<0.05). According to the ROC curve study, the blood serum amyloid A, CRP, procalcitonin, and IFN-β2 levels’ areas under the curve for predicting a poor AP prognosis were 0.859, 0.851, 0.811, and 0.802, all of which had some predictive value. [Conclusion] serum amyloid A, CRP, procalcitonin, and IFN-β2 levels show a strong prognostic value for AP patients’ prognosis and are positively connected with the severity of AP.